Beyond the Usual Suspects: Abdominal Wall Metastases in Prostate Cancer Diagnosed by 68Ga-PMSA PET/CT - Sharjeel Usmani; Khulood Al Riyami; Anjali Jain; Zahida Niaz; Raza Sayani; Shah P Naumani (Journal of the Pakistan Medical Association, 2025)
68Ga-PMSA PET imaging has revolutionized both diagnosis and radioligand therapy selection in patients with metastatic prostate cancer. We report the case of a 63-year-old man with prostate adenocarcinoma who underwent radical prostatectomy followed by radiation therapy and ADT. Found to have rising PSA levels and referred for 68Ga- PSMA PET/CT for restaging. 68Ga-PSMA PET/CT showed multiple suspicious 68Ga-PSMA PSMA avid mediastinal lymph nodes and an avid lesion in the right lower anterior abdominal wall; suspicious for metastasis. Ultrasonography guided biopsy showed metastatic prostate adenocarcinoma. In our cases, 68Ga-PSMA PET/CT identified the unexpected metastatic site which leads to change patient management and potentially improving patient outcome. Keywords: 68Ga-PSMA PET/CT; prostate cancer; anterior abdominal wall metastasis.